PENGARUH LIKUIDITAS, PROFITABILITAS, STRUKTUR MODAL, DAN PENILAIAN PASAR TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017 - 2019 - Putu Gana Setiawan; Tiara Kusuma Dewi; I Putu Agus Atmaja Negara (Universitas Triatma Mulya, 2021)
This research aims to determine the effect of Liquidity, Profitability, Capital Structure, and Market Valuation variables on Stock Returns in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 Period. The reason for choosing food and beverage companies is because food and beverage companies have profitable prospects and their shares are the most resistant in facing economic crises, one of which is the COVID-19 pandemic. The population in this research is food and beverage companies that already exist and are still listed on the Indonesia Stock Exchange for the 2017-2019 period, which consists of 26 companies. The sampling technique used in this research was purposive sampling so that it consisted of 12 companies as research samples. The data analysis technique used in this study uses the classical assumption test and multiple linear regression. The test results show that the variables of Liquidity, Profitability, Capital Structure, and Market Valuation have a positive effect on stock returns.